Asymmetric Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Behavioral and EEG asymmetry and asynchrony of 8,680 infantile spasms were analysed in a review of 75 consecutive video-EEG recordings performed at UCLA Medical Center, Los Angeles from 1982 to 1992.